Control charts in financial applications: An overview. (10th August 2021) - Bisiotis, Konstantinos; Psarakis, Stelios; Yannacopoulos, Athanasios N.
Abstract: Statistical process control (SPC) methods have been widely popular not only in industrial applications but also in recent years in several nonindustrial scientific areas. The basic tools of SPC are control charts. SPC methods have been applied to various financial applications such as portfolio surveillance, stock trading, and interest rates. The purpose of this paper is to present the main applications of statistical monitoring process methods, specifically control charts, to the financial area. We focus on applications in stock markets such as technical trading rules, portfolio monitoring problems providing some directions for future research.